Pelaksanaan Kurikulum Pendidikan Islam dalam Menanamkan Nilai-Nilai Ekoteologis di Sekolah - Risma Nurlela; Bilal Zakawali Al-Fathoni; Fahren Sepujan Nasution; Sarbini; Saca Suhendi; Tatang Muh Nasir; Zohaib Hassan Sain (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This research aims to explore the role of the Islamic Education (PAI) curriculum in cultivating eco-theological values among students. The environmental crisis today is not only ecological in nature but also rooted in moral and spiritual dimensions. In the context of Islamic education, humans are entrusted as khalifah fil-ardh guardians of the earth responsible for maintaining harmony and sustainability in nature. The study employs a qualitative descriptive approach using a library research method, with data collected from academic journals, textbooks, and curriculum documents. The analysis emphasizes the curriculum’s potential to integrate eco-theological principles into learning processes. The findings reveal that the PAI curriculum can effectively embed eco-theological values through the integration of teaching materials, the habituation of environmentally conscious behavior, and project-based learning that nurtures Islamic ecological responsibility. Furthermore, the Merdeka Curriculum offers broader opportunities for developing faith-based and virtuous character education that includes environmental care as a form of devotion to Allah SWT. The implications highlight that incorporating eco-theology into Islamic Education strengthens moral and ecological awareness while supporting sustainable educational practices. This paper includes 42 scholarly references, along with supplementary tables and conceptual illustrations.